Development of Joining Techniques for Carbon Fiber Based Polymer Matrix Composites - Tanoğlu, Metin; İplikçi, Hande (Izmir Institute of Technology, 2020)
In recent years, adhesive bonding has been a promising joining technology for CFRP composites. An appropriate treatment of surfaces for adhesive bonding is one of the effective factors for obtaining a high-quality adhesion strength. However, the adhesion strength is decreased by contaminants, like release agents, as well as an excess of matrix in the top layer. The contact of the adhesive with the reinforcing element is critical. Therefore, it is necessary to make a pre-preparation process on the adherent surface. One of the surface treatments preferred due to the advantages it provides is laser processing. The joint area strength of CFRP (carbon fiber reinforced polymer) composite can be enhanced with laser surface treatment. In this work, the carbon fiber/epoxy composites surface treatment by a nanosecond (1064nm wavelength) laser has been investigated. The polymer layer (epoxy matrix) on the CFRP (carbon fiber reinforced polymer) composite surface was selectively removed by laser treatment to expose carbon fibers. In order to remove the epoxy from the surface sufficiently, laser surface modification parameters were investigated and their effects were examined. These parameters are laser power, frequency, scanning speed and offset distance, respectively. Epoxy removal and fibers damage was analyzed by optical microscope and SEM (scanning electron microscope). Contact angle tests were carried out to analyzed wettability effect on the laser parameters. Lap shear, charpy impact and double cantilever beam (DCB) tests were performed to examine the effect of laser surface modification on mechanical performance.
Karbon Fiber Esaslı Polimer Matriks Kompozitler için Birleştirme Tekniklerinin Geliştirilmesi
Thesis (Master)--Izmir Institute of Technology, Mechanical Engineering, Izmir, 2022
Text in English; Abstract: Turkish and English
Includes bibliographical references (leaves. 61-65)
Keywords: Carbon fibers; Polymer matrix composites; Carbon fiber reinforced polymer; Joining technology